Piperazine-1,4-diium bis[tetrachloridoaurate(III)] dihydrate - Polishchuk, Anna V. (International Union of Crystallography, 2009)
In the title compound, (C(4)H(12)N(2))[AuCl(4)](2)·2H(2)O, the Au(III) atom has a square-planar geometry. The piperazinium dication lies on an inversion centre and adopts a typical chair conformation. In the crystal, a combination of N—H⋯O, N—H⋯Cl and O—H⋯Cl hydrogen bonds results in the formation of a three-dimensional network.